Use of lung ultrasound in school-aged children with wheezing - Attanasi, Marina; Sferrazza Papa, Simone; Porreca, Annamaria; Sferrazza Papa, Giuseppe F.; Di Filippo, Paola; Piloni, Francesca; Dodi, Giulia; Sansone, Francesco; Di Pillo, Sabrina; Chiarelli, Francesco (Frontiers in Pediatrics, 2023)
Background: There is poor information on bedside fast and safe tools which could address the clinicians to establish whether the pathological process underlying to the wheezing is due to asthmatic exacerbation, asthmatic bronchitis or pneumonia. The study aim was to characterize Lung Ultrasound (LUS) in school-aged children with wheezing and evaluate its use for their follow-up. Materials and Methods: We carried out a cross-sectional study including 68 consecutive outpatients (mean age 9.9 years) with wheezing and suggestive signs of an acute respiratory infection. An expert sonographer blinded to all subject characteristics, clinical course and the study pediatrician’s diagnosis, performed LUS after spirometry and before BDT. The severity of acute respiratory symptoms was performed using the Pediatric Respiratory Assessment Measure (PRAM) score. Results: LUS was positive in 38.2% (26/68) patients [12(46.1%) multiple B lines, 24(92.3%) consolidation, 22(84.6%) pleural abnormalities]. In patients with pneumonia, asthmatic bronchitis, and asthma, the proportion of positive LUS were 100%, 57.7% and 0%, respectively. Of note, patients with positive LUS were associated with increased need for hospital admission (30.8% vs 2.4%, p=0.001), administration of oxygen therapy (14.6% vs 0%, p=0.009), oral corticosteroids (84.6% vs 19.0%, p<0.001) and antibiotics (88.5% vs 11.9%, p<0.001), and higher median value of PRAM score (4.0(2.0-7.0) vs 2.0(1.0-5.0); p <0.001). Conclusions: Our findings would suggest the use of LUS as safe and cheap tool used by the clinicians to define the diagnosis in school-aged children with wheezing of unknown causes.